Synthetic approaches for cyclohexane-1, 3-diones: A versatile precursor for bioactive molecules. Issue 17 (2nd September 2021) - Sharma, Dharminder; Kumar, Manish; Das, Pralay
Abstract: Cyclohexane-1, 3-dione derivatives are considered as a key structural precursor for the synthesis of plethora of synthetically significant compounds such as 4 H -chromenones, 2 H -xanthenones, coumarins, enaminones, acridinedione, 1, 4-dihydropyridine, different other heterocycles, and natural products. These compounds show the diverse range of biological activities that include herbicidal, pesticidal, anti-bacterial, anti-inflammatory, anti-tumor, analgesic, anti-convulsant, anti-viral, anti-plasmodial, anti-malarial, anti-allergic, anti-cancer, etc. This versatility in the chemistry of cyclohexan-1, 3-dione and its derivatives is due to the presence of highly active methylene moiety and its active di-carbonyl groups. There are only few reviews in the literature published on the synthetic application of cyclohexane-1, 3-diones, but not on the synthesis of cyclohexane-1, 3-dione and its derivatives. Keeping the importance of cyclohexane-1, 3-dione derivatives in view, we inspired to do a compilation of their synthetic methods from different precursors, which are mainly published in last two decades. Graphical Abstract: UF0001